Synthesis and mechanical properties of porous metals with inverted dealloying structure. (15th March 2022) - Hu, Wen-Kai; Liu, Ling-Zhi; Zou, Lijie; Shao, Jun-Chao; Wang, Shao-Gang; Jin, Hai-Jun
Graphical abstract: Abstract: Dealloyed porous or nanoporous materials often suffer from impaired strength and stiffness due to the pinch-off or spheroidization of ligaments. Herein a crucibleless liquid metal dealloying (CLMD) procedure was developed to prepare bicontinuous Cu-Cr and Ag-Ni composites consisting of a network-like dealloying structure (Cr or Ni) and a solidified matrix of liquid-metal corrosion media (Cu or Ag). Chemical dissolution of the backbone phase of dealloying structure leaves behind the porous-structured matrix phases (Cu or Ag), which is in fact the inverse replica of the dealloyed network structure. The relative strength and stiffness of porous Cu and Ag are higher than those with dealloying structure (e.g., porous Fe 80 Cr 20 ) of similar relative density. Compared with the solid network originally formed in dealloying, the mechanical efficiency of inverted dealloying structure is higher and less sensitive to the above-mentioned topology defects. The ease of CLMD method and the improved mechanical stability of obtained porous materials might enable practical application in many areas.